A Biocatalytic Cascade in an Ultrastable Mesoporous Hydrogen‐Bonded Organic Framework for Point‐of‐Care Biosensing. Issue 44 (30th September 2021) - Tang, Zhuopeng; Li, Xinyi; Tong, Linjing; Yang, Huangsheng; Wu, Jiayi; Zhang, Xiliu; Song, Ting; Huang, Siming; Zhu, Fang; Chen, Guosheng; Ouyang, Gangfeng
Abstract: Herein, we report the first example of using mesoporous hydrogen‐bonded organic frameworks (MHOFs) as the protecting scaffold to organize a biocatalytic cascade. The confined microenvironment of MHOFs has robust and large transport channels, allowing the efficient transport of a wide range of biocatalytic substrates. This new MHOF‐confined cascade system shows superior activity, extended scope of catalytic substrates, and ultrahigh stability that enables the operation of complex chemical transformations in a porous carrier. In addition, the advantages of MHOF‐confined cascades system for point‐of‐care biosensing are also demonstrated. This study highlights the advantages of HOFs as scaffold for multiple enzyme assemblies, which has huge potential for mimicking complex cellular transformation networks in a controllable manner. Abstract : A mesoporous hydrogen‐bonded organic framework (MHOF)‐confined biocatalytic cascade nanoreactor is constructed. This MHOF cascade nanoreactor has robust and large transport channels, allowing the efficient diffusion of a wide range of biocatalytic substrates and displays the advantages of superior activities, extended scope of substrates, and ultrahigh stability that enables mimicking intracellular signal communications and complex chemical transformations.